2012
DOI: 10.1073/pnas.1212079109
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and morphological diversity of passerine birds

Abstract: The relationship between species richness and the occupation of niche space can provide insight into the processes that shape patterns of biodiversity. For example, if species interactions constrained coexistence, one might expect tendencies toward even spacing within niche space and positive relationships between diversity and total niche volume. I use morphological diversity of passerine birds as a proxy for diet, foraging maneuvers, and foraging substrates and examine the morphological space occupied by reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(174 citation statements)
references
References 52 publications
12
155
2
5
Order By: Relevance
“…The increase in morphodensity, as with volume, was no greater than expected under the null model, perhaps implying that trait packing and expansion contribute equally to the gradient in richness. However, across all elevations, most species were concentrated within a central core region of trait space, with the density of species declining rapidly towards the periphery [37]. Thus, increases in trait volume were driven by a relatively small number of species with extreme phenotypes, while most (78%) of the additional diversity in the lowlands was accommodated within a volume of functional trait space equivalent to that occupied in the highlands.…”
Section: H M H M Hmentioning
confidence: 94%
See 2 more Smart Citations
“…The increase in morphodensity, as with volume, was no greater than expected under the null model, perhaps implying that trait packing and expansion contribute equally to the gradient in richness. However, across all elevations, most species were concentrated within a central core region of trait space, with the density of species declining rapidly towards the periphery [37]. Thus, increases in trait volume were driven by a relatively small number of species with extreme phenotypes, while most (78%) of the additional diversity in the lowlands was accommodated within a volume of functional trait space equivalent to that occupied in the highlands.…”
Section: H M H M Hmentioning
confidence: 94%
“…The use of normalized PC trait axes when quantifying assemblage morphospace assumes that each trait axis is of similar importance in charactering avian niche space [36,37]. To test this assumption, we estimated the contribution of each PC trait in predicting guilds by removing each axis as a term from the model and calculating the drop in classification accuracy.…”
Section: (D) the Relationship Between Morphology And Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have shown different levels of species packing or grouping, including the presence of empty morphospace zones (Gatz 1979;Goatley et al 2010;Ricklefs 2012). The degree of species packing seems to coincide with the morphologies that are best adapted for the most efficient exploitation of resources in the ecosystem (Schoener 1974;Gatz 1979;Wainwright and Richard 1995;Ricklefs 2012).…”
Section: Interpreting the Otolith Morphospacementioning
confidence: 99%
“…According to the concept of limiting similarity, species have a minimum distance in a one-dimensional niche space (MacArthur and Levins 1967), which should lead to regular spacing of species within morphospace (Ricklefs 2012). However, many studies have shown different levels of species packing or grouping, including the presence of empty morphospace zones (Gatz 1979;Goatley et al 2010;Ricklefs 2012).…”
Section: Interpreting the Otolith Morphospacementioning
confidence: 99%